Nano-scale Biophysical and Structural Investigations on Intact and Neuropathic Nerve Fibers by Simultaneous Combination of Atomic Force and Confocal Microscopy - Rosso, Gonzalo; Liashkovich, Ivan; Young, Peter; Shahin, Victor (Frontiers in Molecular Neuroscience, 2017)
The links between neuropathies of the peripheral nervous system (PNS), including Charcot-Marie-Tooth1A and hereditary neuropathy with liability to pressure palsies, and impaired biomechanical and structural integrity of PNS nerves remain poorly understood despite the medical urgency. Here, we present a protocol describing simultaneous structural and biomechanical integrity investigations on isolated nerve fibers, the building blocks of nerves. Nerve fibers are prepared from nerves harvested from wild-type and exemplary PNS neuropathy mouse models. The basic principle of the designed experimental approach is based on the simultaneous combination of atomic force microscopy (AFM) and confocal microscopy. AFM is used to visualize the surface structure of nerve fibers at nano-scale resolution. The simultaneous combination of AFM and confocal microscopy is used to perform biomechanical, structural and functional integrity measurements at nano- to micro-scale. Isolation of sciatic nerves and subsequent teasing of nerve fibers take approximately 45 minutes. Teased fibers can be maintained at 37°C in a culture medium and kept viable for up to 6 hours allowing considerable time for all measurements which require 3-4 hours. The approach is designed to be widely applicable for nerve fibers from mice of any PNS neuropathy. It can be extended to human nerve biopsies.